Re-reading The Red Tree: The art of Shaun Tan - Sikorska, Magdalena (Nordic Journal of English Studies, 2018)
This article re-reads The Red Tree by Shaun Tan in the light of literary and art criticism. Discussing Tan’s work as both thoroughly contemporary and richly dialogic with earlier epochs, it attempts to disentangle the clues of past and present interwoven into the powerfully resonant narrative. Not radically challenging the main interpretative lines, it offers alternatives to the widely accepted readings of this picturebook.